TOPSIS Analysis of Changes of Quality of Human Capital in European Union Countries - Adam P. Balcerzak; Michal Bernad Pietrzak (Institute of Economic Research (IER), 2016)
Purpose of the article: In the case of highly developed countries quality of human capital (QHC) is currently considered as one of the most important factors determining international competitiveness and growth of economies. The fundamental role of the QHC can be seen in the EU policy documents such as Europe 2020 strategy. In this context the main purpose of the article is to evaluate the QHC in the EU countries at the macroeconomic level and to make comparison between so called 'new' member states that joined the EU after the year 2004 and the 'old' EU countries. Methodology/methods: QHC is considered as a multidimensional phenomenon. As a result, in the research Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied. The method enables to evaluate the objects in terms of economic phenomena that have multidimensional character based on the set of detailed economic attributes (variables). In the research eight diagnostic variables were used. The synthetic index describing the relative level of QHC in the analysed economies was estimated, which enabled to propose a rating of the countries and group them into homogenous subsets. Scientific aim: The scientific aim of the article was to evaluate the progress obtained by the 'new' member states after joining the EU. As a result, two ratings grouping the EU countries from the once with the highest level of QHC to the once with its lowest level in the year 2004 and 2012 were determined. Findings: The comparison of the ratings in the year 2004 and 2012 shows that most of the 'new' member states have made a significant progress in the analysed period. Conclusions: The conducted multidimensional research enabled to quantify QHC in the EU countries in the year 2004 and 2012 with application of multidimensional perspective. As a result it enabled to evaluate the changes of that phenomenon in the period and to point the countries that are the leaders in the field.
Keywords: C38; E24; 330; Quality of Human Capital; macroeconomic perspective; TOPSIS method; European Union countries